Fabrication, structure and properties of epoxy/metal nanocomposites - Ma, Jun; Bao La, Ly Truc; Zaman, Izzuddin; Meng, Qingshi; Luong, Lee; Ogilvie, Denise; Kuan, Hsu-Chiang (Wiley, 2011)
Gd2O3 nanoparticles surface-modiﬁed with IPDI were compounded with epoxy. IPDI provided an anchor into the porous Gd2O3 surface and a bridge into the matrix, thus creating strong bonds between matrix and Gd2O3. 1.7 vol.-% Gd2O3 increased the Young’s modulus of epoxy by 16–19%; the surface-modiﬁed Gd2O3 nanoparticles improved the critical strain energy release rate by 64.3% as compared to 26.4% produced by the unmodiﬁed nanoparticles. The X-ray shielding efﬁciency of neat epoxy was enhanced by 300–360%, independent of the interface modiﬁcation. Interface debonding consumes energy and leads to crack pinning and matrix shear banding; most fracture energy is consumed by matrix shear banding as shown by the large number of ridges on the fracture surface.